SOME COMMON SPECIES OF PLANKTONIC HARPACTICOIDA (CRUSTACEA, COPEPODA) FROM INDONESIAN WATERS - Mulyadi Ningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Taxonomic study was made on the species of the order Harpacticoida recently collected from 9 sites in Indonesian waters. Six species from 5 genera and 5 families Clytemnestridae, Ectinosomatidae, Harpacticidae, Tachidiidae and Talestridae, including Clytemnestra scutellata (Dana, 1847); Euterpina acutifrons (Dana, 1848), Eudactylopus latipes (T. Scott, 1894); Macrosetella gracilis (Dana, 1848); Microsetella norvegica (Boeck, 1864) and Microsetella rosea (Dana, 1852) were recorded. C. scutellata and M. norvegica are recorded for the first time from Indonesian waters. Descriptions, measurements, and figures are given for all species, along with a review of their distribution over the world’s oceans, with taxonomical remarks, and restricted synonymies